2022
DOI: 10.3390/nu14234968
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Efficacy and Mechanism of Astragalus membranaceus on High Altitude Polycythemia by Integrating Network Pharmacology and In Vivo Experiments

Abstract: Hypoxic exposure makes plateau migrators susceptible to high altitude polycythemia (HAPC). Astragalus membranaceus (AM) is an edible and medicinal plant with remarkable immunomodulatory activities. The purpose of this study was to discover if AM could be a candidate for the prevention of HAPC and its mechanism. Here, network pharmacology was applied to screen active compounds, key targets, and enriched pathways of AM in the treatment of HAPC. Molecular docking evaluated the affinity between compounds and core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The BC and CC represented the shortest path crossing a single node and the ease of communication between nodes. A value greater than twice the median of Degree and the median of the BC and CC was used as the criterion to screen the core compound targets of Scutellaria baicalensis and disease and to create a PPI network interaction map [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BC and CC represented the shortest path crossing a single node and the ease of communication between nodes. A value greater than twice the median of Degree and the median of the BC and CC was used as the criterion to screen the core compound targets of Scutellaria baicalensis and disease and to create a PPI network interaction map [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…[2,3] It has also been found that HAPC is closely related to hematopoietic factors and inflammatory factors. [3,4] HAPC can cause blood vessel damage, microvascular lesions, cerebral arteriosclerosis, cerebral perfusion, cerebral metabolism, and inflammatory responses in the brain promoting the release of inflammatory cytokines, peripheral blood cells, and peripheral blood of inflammatory cytokines, also changing the permeability of the blood-brain barrier and promoting inflammation factors and white blood cells into the brain, with decreased cognitive function. [5][6][7] At present, there are few reports on the correlation between inflammatory factors and cognitive impairment in patients with polycythemia in altitude hypoxia environments worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…However, absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of many herbal products are too poor to bind the putative targets in the lesions sufficiently, especially in the brain [5][6][7]. In this regard, most studies exclude the ingredients with low oral bioavailability (OB), drug-likeness (DL), or blood-brain barrier (BBB) permeability to reduce the false positive results in network pharmacology [8][9][10][11][12]. However, this strategy ignored the therapeutic effects and mechanisms of the low-OB compounds.…”
Section: Introductionmentioning
confidence: 99%